2002
DOI: 10.1063/1.1499515
|View full text |Cite
|
Sign up to set email alerts
|

Magnon modes for thin circular vortex-state magnetic dots

Abstract: The magnetization in a magnetic microdot made from soft magnetic materials can have a vortexlike ground state structure resulting from competition between the exchange and dipolar interactions. Normal mode magnon frequencies for such dots are calculated taking into account both exchange and magnetostatic effects. The presence of a low-lying mode as well as doublet structure with small splitting is demonstrated. Estimates of the mode frequencies for permalloy dots are obtained, and the possibility of experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 10 publications
8
79
2
Order By: Relevance
“…Recently, the dynamics of magnetic vortices and vortex cores in thin-film elements has been intensively studied. 2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] In this context, the present study of the dynamics of a 3D vortex structure can be considered as an extension of the previous knowledge on this topic.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Recently, the dynamics of magnetic vortices and vortex cores in thin-film elements has been intensively studied. 2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] In this context, the present study of the dynamics of a 3D vortex structure can be considered as an extension of the previous knowledge on this topic.…”
Section: Introductionmentioning
confidence: 81%
“…Several studies on magnetic excitations in various thinfilm elements have been reported, including wires, [3][4][5][6][7] rectangles, 4,[8][9][10] circular disks 2,[11][12][13][14][15][16][17][18][19] and squares [20][21][22][23][24] with closure domains, rings, 25 and several other elementary shapes. In all examples listed above, the samples studied were essentially two-dimensional ͑2D͒, i.e., thickness effects are not important as far as the profile of the dynamic mode is concerned.…”
Section: Introductionmentioning
confidence: 99%
“…This choice is motivated above; one more reason is that such an effective term can be used to model the magnetic dipole interaction. 33 The function φ(ρ, χ) may have singularities inside the disk Ω. Minimal configurations for the energy (4) are constructed from solution of the respective EulerLagrange equations, which is the scalar Laplace equation…”
Section: A Strong Border Anisotropy In a Continuum Approachmentioning
confidence: 99%
“…In principle, the gyrotropic vortex motion modulates the boundary conditions for the magneto-static modes and leads to an interaction between gyrotropic and magnetometric modes [19]. This interaction leads to a splitting of the MSBVlike modes and is discussed in [20].…”
Section: Introductionmentioning
confidence: 99%